II. In the Educational Journals of the Constitutional Period Teacher Qualifications - KENAN, SEYFİ (ILEM, 2022)
Darulmuallimin was established in 1848 with the aim of training the teachers needed by the new modern schools that were opened since the start of the 19th century. When addressing the Second Constitutional Era, significant changes had been experienced in the understanding of teacher training processes. Drastic adjustments had been made regarding teacher development as a professional occupation and the formation of the standards of the teaching profession. Believing that the recovery of the empire that had begun to splinter could be realized through education, intellectuals an educators engaged in lively debate over identifying the teacher competencies they felt had the most critical role in education. This study involves the debates that had been taken up in education journals published in Istanbul regarding how to develop the teaching profession and identify its professional competencies during the Second Constitutional Era. The debates placed emphasis on issues such as the accumulations teachers possess in various disciplines, the progressive approach, the discovery approach, the connections lessons have with life, and professional experience. When generally assessing teachers' views related to teachers' mission and qualifications, the Second Constitutional Era is seen to have some striking similarities with today's literature on teacher competencies. In this respect, the ideas on education in the Second Constitutional Era can be said to have been a significant source of what was imagined for teachers in the Republican Era.
Keywords: Teacher competencies; Second Constitutional period teacher training; teacher values and attitudes; education journals